The Differences of Urban Innovation Strategies Implementations in Bandung City, West Java and Malang City, East Java - Yusniah Anggraini (Inovbook Publications, 2021)
Quality city infrastructure is currently the main requirement. Because the city is a place to live, currently connected globally but not connected locally, so that in order to become a livable city, the city must be able to provide a decent living for its citizens while maintaining environmental quality. One way to improve the quality of the city is to carry out urban innovations, one of which can be by focusing on parks and paying attention to the environment. The two cities studied in this study are Bandung City, West Java, and Malang City, East Java, by looking at government innovation on environmental sustainability in it. The goal is to identify differences in innovation in each city studied. The research was conducted using descriptive qualitative methods. The results show that if the city of Bandung provides more innovation in the form of building thematic parks to increase the capacity of green open space in the city of Bandung, the city of Malang provides more innovation in the form of technology to manage green open space and other urban spaces so that later it can be monitored by the entire city community and if you want to build buildings, can determine a location that does not interfere with managed spaces such as parks. This is because Malang City has arguably enough RTH to support people's lives and the environment, so that the innovations carried out can be one step ahead of Bandung City. The hope for the future is that every city will always maintain the innovations that have been implemented and carry out real steps and also improve technology, resources, and so on.